The Activities of the Internal Troops of the Ministry of Internal Affairs, Internal Affairs Authorities of Russia and International Humanitarian Law - I. I. Кotlyarov; C. L. Khodzhabegova (Московский журнал международного права, 2008)
It is stated in the article that from the formal point of view treaties in respect of the international humanitarian law (IHL), to which Russia is a member, are addressed to the state armed forces, which are the basis of the defense of the Russian Federation According to the art 1 item 5 of the federal law «about the Defense» the defense of the state is also provided by the internal troops of the Ministry of internal affairs of Russia. The principles and norms of IHL should be fully used in respect of these troops during the armed actions.During the international armed conflict norms of the IHL also cover: internal affairs authorities of Russia if they are included in the Russian armed forces; internal affairs authorities’ personnel, which takes part in UN peacekeeping operations, protects the rights and interests of the civilians during armed conflicts including fugitives and stateless persons, provides assistance in searches, conducted by the members of the families dispersed by war, and also searches of persons who committed serious breaches of the norms of international humanitarian law.